Altered stimulus frequency and intensity dependence of the somatosensory evoked potential in rats after acute application of two mitochondrial toxins - Takács Szabolcs (Acta biologica Szegediensis, 2009)
Mitochondrial toxins are a special group of toxicants with nervous system effects. The resulting nervous system damage could be detected and followed-up by means of functional biomarkers but these still have to be worked out. In this work, adult male Wistar rats were anesthetized with urethane, the left hemisphere was exposed, and a silver recording electrode was placed on the projection area of the whiskers. The whisker pad was stimulated with electric square pulses and the cortical response was recorded. The intensity of the stimulus was varied between 25% and 100% (just supramaximal), and its frequency, between 1 and 10 Hz. Control records were taken, then one of the agents (3-nitrporopionic acid, a mitochondrial toxin of microfungal origin: 20 mg/kg b.w.; or manganese, a heavy metal: 50 mg/kg b.w. in chloride form) was injected ip. and further records were taken. Both agents had an effect on the latency, but on the amplitude, only Mn. Of the relationships between stimulation settings and evoked potential parameters, frequency dependence of latency had the clearest alteration on application of Mn or 3-NP. Such effects may have the potency to be developed to functional biomarkers, applicable in practical toxicology or in animal research.